Integrating External Commodity Information into Standard Cost Review during Supply Disruptions: Insights from Rubber Expansion Joint Manufacturing - Azimi Faqqihuddin Arsyad; Mochamad Fahru Komarudin; Azimi Faqqihuddin Arsyad (LPPM Universitas Banten jaya, 2026)
This study examines how publicly available commodity and macroeconomic information can be integrated into standard cost review during supply disruptions in rubber expansion joint manufacturing. Using an exploratory case study and conceptual design approach, the paper maps external market signals to key cost drivers to support earlier managerial responses under volatile input conditions. The study identifies natural rubber, synthetic rubber derivatives, imported additives, freight, and exchange rates as critical exposure points. It proposes a three-layer mechanism consisting of signal detection, managerial interpretation, and decision response to trigger partial or full standard cost review before internal variance reports become available. The findings indicate that external indicators, including commodity prices, JISDOR exchange rates, and producer price indices, can function as a supplementary control interface for management accountants. The study concludes that external information improves the timeliness of pricing and cost-review decisions during market instability, although it should complement rather than replace internal cost data. The proposed framework contributes to strategic management accounting by strengthening cost control responsiveness during disruptions.